MMP-9 Activation via ROS/NF-κB Signaling in Colorectal Cancer Progression: Molecular Insights and Prognostic–Therapeutic Perspectives - Andrej Veljkovic; Goran Stanojevic; Branko Brankovic; Stefanos Roumeliotis; Konstantinos Leivaditis; Branka Djordjevic; Xiaobo Li; Aleksandra Klisic; Jovan Hadzi-Djokic; Gordana Kocic (Current Issues in Molecular Biology)
Colorectal cancer (CRC) is characterized by complex interactions between inflammation, oxidative stress, and extracellular matrix remodeling. Recent studies have highlighted the significance of the reactive oxygen species (ROS)–nuclear factor kappa B (NF-κB)–matrix metalloproteinase-9 (MMP-9) axis in promoting tumor invasion and metastasis in CRC, linking oxidative stress with inflammatory signaling and extracellular matrix degradation. In this study, we analyzed the concentration of advanced oxidation protein products (AOPPs), expression of NF-κB, and the activity of MMP-9 in tumor tissue, adjacent tissue, and healthy control colon tissue. Tissue specimens were collected from 50 patients with primary CRC following surgical resection. The analyses were performed using appropriate and validated biochemical methods, including ELISA, spectrophotometry, and indirect immunofluorescence. Significantly higher levels of all three markers were observed in tumor tissue compared to controls. Additionally, adjacent tissue exhibited elevated NF-κB expression and MMP-9 activity when compared to healthy colon tissue. AOPP levels correlated strongly with MMP-9 activity, highlighting the role of oxidative stress in the activation of MMP-9. MMP-9 demonstrated the highest predictive value for CRC, emphasizing its potential as a diagnostic and theranostic marker. Our findings support the hypothesis that the ROS–NF-κB–MMP-9 axis plays an important role in CRC progression, particularly during stages T2 and T3. Targeting this pathway may offer new therapeutic strategies for limiting tumor invasion and recurrence. Moreover, ensuring adequate surgical resection margins is crucial to optimizing treatment outcomes.